Analisis Reward terhadap Komitmen Afektif melalui Kepuasan Kerja Karyawan Emdee Skin Clinic - Agus Budhi Santosa; Erwin Tjahjuadi (Sekolah Tinggi Ilmu Ekonomi Yapan, 2022)
Employees are an important component in a company, related to how the company can achieve its goals. The purpose of this study was to determine the effect of reward on employee commitment through perceived satisfaction. The object used in this research is Emdee Skin Clinic in Surabaya. Data collection is specifically carried out by distributing questionnaires to the research sample. The sample was determined using non-probability sampling technique and obtained as many as 45 employees as research respondents. The analytical method used is smart PLS. Based on the test results, the conclusions that can be drawn in this study are Rewards make a positive contribution to Affective Commitment, Satisfaction makes a positive contribution to Affective Commitment, Rewards make a positive contribution to Satisfaction.